Comparison of hematological parameters between single and twin pregnancies in Dorper ewes during gestation, lambing, and postpartum - Santarosa, Bianca Paola [UNESP] (2022)
The hematopoietic system changes during the pregnancy to carry fetal development and maternal needs. This study compared the hematological parameters between ewes with single and twin pregnancies during gestation, delivery, and postpartum. The experiment was conducted on 60 healthy pregnant Dorper ewes that were divided into two experimental groups: Group 1 (G1), with single pregnancies (n=30), and Group 2 (G2), with twin pregnancies (n=30). Blood samples were collected from all ewes at different times: immediately before fixedtime artificial insemination (AI); on day 30, 90, 120, 130, and 140 of pregnancy; immediately after delivery; and at 24h and 48h postpartum. Statistical analysis compared the two groups at different times (P<0.05). Mild, normocytic, and hypochromic anemia was detected in all ewes from AI time and throughout pregnancy from both groups, but did not prove to be of clinical relevance. In the peripartum stage (from the 140th day of pregnancy to 48h postpartum), the ewes with twin pregnancies (G2) exhibited higher erythrogram values and neutrophil:lymphocyte ratio than did ewes with single pregnancies (G1). This indicated a greater hematopoietic adaptation in the body during the development of two fetuses. Except for the eosinophil numbers, all leukogram parameters were influenced by pregnancy in a similar way in both groups, and was characterized mainly by leukocytosis with neutrophilia during peripartum due to the high presence of endogenous cortisol at delivery. Thus, these findings showed that pregnancy was a stressful physiological event that increased the leukocyte count with a slight alteration in the erythrogram of Dorper ewes.